Electro-clinical-pathological correlations in focal cortical dysplasia (FCD) at young ages - Holthausen, Hans; Pieper, Tom; Winkler, Peter; Bluemcke, Ingmar; Kudernatsch, Manfred (Childs Nervous System, 2014)
The prevalence of focal cortical dysplasia (FCD) in pediatric patients with focal epilepsy is not exactly known because authors of publications in which the etiologies of epilepsies are listed, but which are not dealing specifically with epilepsy surgery issues, tend to lump together the many kinds of malformations of cortical development (MCD), of which FCDs, because of their relative frequency, are the most relevant subtypes. Out of 561 patients with MCD (children and adults) operated at centers in Europe who do feed data into the “European Epilepsy Brain Bank,” 426 (76 %) had FCD.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Children; EEG; Electro-clinical-pathological correlations; Epilepsy; Focal Cortical Dysplasia; Seizure semiology